Performance measurement of free-space optical 980 nm channel using multiple sets of environmental conditions - Shah, S. M. A. (Springer Science+Business Media New York, 2015)
In this paper the performance of the free space optics (FSO) based communication link is investigated in hot and dry weather which is a common atmospheric condition in Pakistan. To measure the performance of connectivity at different day time, a portable test-bed setup is launched to describe the performance of 980 nm FSO in hot and dry weather at various distances with a large aparture of transmitter and receiver. This test bed is capable to evaluate performance in terms of data transmission and signal strength with bit error rate. The results show that perfect alignment is a main concern along with data transmission and signal strength. The transmission performance is different during the day and the night time. Moreover the results also show the performance of FSO at the indoor is up to the mark and very little or no jerks in the streaming data considering perfect alignment and a short distance. The FSO at short distance can be aligned perfectly without the alignment tools. However, for longer distance, it requires to be perfectly aligned with the tool. In case of perfect alignment and clear weather, the transfer rate is up to the mark, but the signal strength varies during the day and the night time which causes the delay in the transmission. The performance analysis shows that the improvement of transmission channel is possible at the night time.